2003
DOI: 10.1038/sj.leu.2403070
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance induction by costimulator blockade in 100 cGy treated hosts with varying degrees of genetic disparity

Abstract: Long-term multilineage allochimerism can be obtained in H2-mismatched B6.SJL to BALB/c transplants with host irradiation of 100 cGy, donor spleen cell pre-exposure and costimulator blockade with anti-CD40 ligand (CD40L) antibody. We evaluated this allochimerism approach in murine marrow transplants with different degrees of major histocompatibility complexe (MHC) mismatching; these include: (1) H2-mismatched transplant H2Kk to H2Kb, (2) full haplo-identical transplant H2Kbd to H2Kbk, (3) a partial haplo-identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Manipulation of the dose and schedule of marrow infusions has allowed us to drop the irradiation altogether [103]. Further work has shown, not surprisingly, that lesser degrees of H2 incompatibility resulted in improved alloengraftment results [104].…”
Section: Minimal or Nonmyeloablative Allogeneic Transplantation (Mouse)mentioning
confidence: 99%
“…Manipulation of the dose and schedule of marrow infusions has allowed us to drop the irradiation altogether [103]. Further work has shown, not surprisingly, that lesser degrees of H2 incompatibility resulted in improved alloengraftment results [104].…”
Section: Minimal or Nonmyeloablative Allogeneic Transplantation (Mouse)mentioning
confidence: 99%
“…Interestingly, when 200 million cells were infused at time 0, there was essentially no engraftment, so that scheduling was a critical component of engraftment. Most recently, we have shown that with lesser degrees of H-2 histoincompatibility there are higher levels of engraftment [9].…”
Section: Engraftment In Nonmyeloablated Micementioning
confidence: 99%